Socio-Economic Implications of COVID-19 Pandemic in South Asia: Emerging Risks and Growing Challenges - Rasul, Golam; Nepal, Apsara Karki; Hussain, Abid; Maharjan, Amina; Joshi, Surendra; Lama, Anu; Gurung, Prakriti; Ahmad, Farid; Mishra, Arabinda; Sharma, Eklabya (Frontiers in Sociology, 2021)
The dramatic spread of COVID-19 has threatened human lives, disrupted livelihoods, and affected trade, economy and businesses across the globe. The global economy has begun to show major disruptions and is heading toward a severe recession with an unprecedented economic crisis. As the global economy is highly integrated and interdependent through the global supply chains, it has been profoundly affected by the COVID-19 pandemic. Although all countries have faced difficulties due to Covid-19, South Asian countries in particular have had to deal with a more challenging situation due to their large population, weak health facilities, high poverty rates, low socio-economic conditions, poor social protection systems, limited access to water and sanitation, and inadequate living space, necessary to maintain physical distancing and take other required measures to contain this pandemic. To contain the spread of the virus, South Asian countries have imposed stringent lockdowns, which have consequently affected the lives and livelihoods of millions of people in the region, where a third of world’s poor live. Against this backdrop, this paper examines the existing and prospective impacts, risks and challenges of Covid-19 on key social and economic sectors including migration, tourism, informal sector, agriculture and rural livelihoods. The analysis revealed that COVID-19 is likely to affect economic growth, increase fiscal deficit and monetary burden, increase the risks of macroeconomic instability, decrease migration and remittance, reduce income from travel and tourism, and result in dwindling micro-small and medium industries and informal businesses. This is likely to deepen poverty and increase unemployment and the risks of hunger and food insecurity. If not addressed properly, this may reinforce existing inequalities, break social harmony, and increase tension and turbulence. The economic and social costs of the COVID-19 outbreak are therefore likely to be significant and long-lasting in South Asia.